Taming Indian Inflation - Cashin, Paul.; Anand, Rahul (Washington, D.C. : International Monetary Fund, 2016)
High and persistent inflation has presented serious macroeconomic challenges in India in recent years, increasing the country's domestic and external vulnerabilities. A number of factors underpin India's high inflation. This book analyzes various facets of Indian inflation-the causes, consequences, and policies being implemented to manage it. Several chapters are devoted to analyzing and managing food inflation, given its significance in driving overall inflation dynamics in India.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet